Legal Awareness of Halal Product Guarantees: The Role of Universities in Indonesia and Malaysia (Lembaga Contrarius Indonesia, 2026)
The purpose of this research is to further examine the role and strategy of universities in building legal awareness of Muslim consumers on the importance of halal product guarantees both related to food, beverages, used goods and other products, so that Muslim consumers feel safe and comfortable in utilizing/consuming the products needed both imported and exported to other regions/countries. In this research, the author uses a qualitative approach that emphasizes the importance of developing and compiling theories that are always rooted in inductive-empirical thinking. Regarding data collection techniques, the author used participant observation, interviews, and secondary data searches. The role of Indonesian and Malaysian Universities in building legal awareness of halal product guarantees, currently focuses on education and training, research and development, and collaboration with government and industry. For the strategies used, the two countries, namely Malaysia and Indonesia, have differences in application. The strategy used by Malaysia is more about strengthening halal legal awareness through a multidisciplinary approach, stronger collaboration with industry, and mature halal infrastructure. Meanwhile, the strategy used by Indonesia at this time is still focused on counseling and socialization, cooperation with the Halal Product Guarantee Agency (BPJPH), and the development of halal infrastructure.